Stopping Tuberculosis in Central Asia : Priorities for Action - Godinho, Joana; Veen, Jaap; Dara, Masoud; Cercone, James; Pacheco, José (Washington, DC: World Bank, 2012)
Stopping Tuberculosis in Central Asia reviews the epidemiological situation, control efforts, and financing of tuberculosis programs in Kazakhstan, Kyrgyz Republic, Tajikistan, and Uzbekistan. It was based on a review of existing statistics and reports, and on consultation with key stakeholders-Governments, NGOs, and donors in Central Asia. This work contributes an agenda for action to address the impending epidemiological crisis that has been posed by the sudden increase in cases of HIV/AIDS infection combined with a prevalent epidemic of TB.